Mon-eenagers Diary (money teenagers diaries) / Nur Hidayah Abdul Halim ... [et al.] - Abdul Halim, Nur Hidayah; Ja’afar, Saidatul Sa’adiah; Anuar, Najwa Maisarah; Mohd Amin, Siti Nadia; Daud, Shahreena (Universiti Teknologi MARA, Kedah, 2023)
Personal financial planning is an important element in the daily life of individuals regardless of age and status. Young people such as generation Z or teenagers are also involved in their personal financial planning. Today's lifestyle greatly affects how teenagers manage their finances. Teenagers has a hard time in controlling their spending and often overspend. The results of the study found that the millennial generation is still at a moderate level in their financial management. (Hassim, N., & Ramli, Z. (2022). Mon-eenagers Diary is a daily assistant diary that makes it easy for teenagers to record and plan their daily and monthly expenses. There are 3 objectives of Mon-eenagers Diary which is to track the daily cashflow, to help teenagers capture every task also goal and the lastly, to identify the strategies on how to achieve the stated goals. The novelty of Mon-eenagers Diary is the uniqueness of the diary itself, which contains very user-friendly and artistic features that attract teenagers to make records and notes. This will encourage them to record their daily cashflow dan set the short-term goals that they want to achieve. This diary can also be carried easily so users can use it anywhere and anytime. Mon-eenagers Diary will certainly make it easier for society especially among teenagers to manage their personal finance in terms of expenses, savings and investments. To some extent, Mon-eenagers Diary can provide guidelines in managing personal finance, avoiding excessive spending and achieving their financial objectives. Mon-eenagers Diary will be commercialized not only among the students of UiTM City Campus, Melaka Branch, but can even be expanded among teenagers in other educational institutions. They are considered as a potential prospect since they are directly involved in daily expenses such as food, study equipment, education fees, housing and transportation.